Efektivitas Penggunaan Strategi Jigsaw Dalam Pembelajaran IPS Materi Pranata Sosial Masyarakat Kelas VIII SMP Negeri 2 Sawit Tahun Ajaran 2014/2015 - Churiyati, Nurul, Drs. Suharjo, M.S (2015)
This study aims to determine the level of understanding of students in learning the material IPS Social Institution in Society class VIII students of SMP Negeri 2 Sawit academic year 2014/2015. The population in this study were all students of class VIII SMP Negeri 2 Sawit totaling 200 students and a sample is taken two classes of class VIII VIII C and G. Each class 1 meetings, learning by using strategies jigsaw. Data collection techniques used is a method of testing, interviews, observation and documentation. Analysis technique use in this study is the Wilcoxon test. Results of research at α = 5%, the result that understanding students learning material IPS social institutions in society that uses a jigsaw strategy to increase the percentage of the value of the results of the average pre-test learning with jigsaw strategy of 81.68%, while the percentage of the average value post test amounted to 90.58%. Jigsaw learning strategies can be used to improve student learning outcomes in social studies learning material social institutions in society class VIII SMP Negeri 2 Sawit.